Blocking SLC7A11 attenuates the proliferation of esophageal squamous cell carcinoma cells - Wen-Ting Li; Xin Jin; Sheng-Jie Song; Chong Wang; Chuang Fu; Wen Jiang; Jie Bai; Zhi-Zhou Shi (Animal Cells and Systems)
The role of ferroptosis-associated gene SLC7A11 in esophageal cancer progression is largely unknown, therefore, the effects of blocking SLC7A11 on esophageal squamous cell carcinoma (ESCC) cells are evaluated. Results showed that SLC7A11 was overexpressed in ESCC tissues both in mRNA and protein levels. Blocking SLC7A11 using Erastin suppressed the proliferation and colony formation of ESCC cells, decreased cellular ATP levels, and improved ROS production. Sixty-three SLC7A11-binding proteins were identified using the IP-MS method, and these proteins were enriched in four signaling pathways, including spliceosome, ribosome, huntington disease, and diabetic cardiomyopathy. The deubiquitinase inhibitors PR-619, GRL0617, and P 22077 could reduce at least 40% protein expression level of SLC7A11 in ESCC cells, and PR-619 and GRL0617 exhibited suppressive effects on the cell viability and colony formation ability of KYSE30 cells, respectively. Erastin downregulated GPX4 and DHODH and also reduced the levels of β-catenin, p-STAT3, and IL-6 in ESCC cells. In conclusion, SLC7A11 was overexpressed in ESCC, and blocking SLC7A11 using Erastin mitigated malignant phenotypes of ESCC cells and downregulated key ferroptosis-associated molecules GPX4 and DHODH. The therapeutic potential of targeting SLC7A11 should be further evaluated in the future.